Is Prescription Nonredemption a Source of Poor Health Among the Roma? Cross-Sectional Analysis of Drug Consumption Data From the National Health Insurance Fund of Hungary - Bekele, Bayu Begashaw; Harsha, Nouh; Kőrösi, László; Vincze, Ferenc; Czifra, Árpád; Ádány, Róza; Sándor, János (Frontiers in Pharmacology, 2021)
Background: The health status of the Roma is inferior to that of the general population. The causes of poor health among this population are still ambiguous, but they include low utilization of healthcare services. Our study aimed to investigate prescription redemptions in segregated Roma colonies (SRC) where the most disadvantaged quartile of Roma people are living. Methods: A cross-sectional study was carried out with data obtained from the National Institute of Health Insurance Fund Management in the settlements belonging to the study area of the “Public Health-Focused Model Program for Organizing Primary Care Services”. The study included 4,943 residents of SRC and 62,074 residents of the complementary area (CA) of the settlements where SRC were located. Crude and age- and sex-standardized redemption ratios for SRC and CA were calculated for each Anatomic Therapeutic Chemical (ATC) group and for the total practice by ATC group. Standardized relative redemptions (RR) with 95% confidence intervals were calculated for SRC, with CA as a reference. Results: The crude redemption ratios were 73.13% in the SRC and 71.15% in the CA. RRs were higher in the SRC than in the CA for cardiovascular, musculoskeletal system, and alimentary tract and metabolism drugs (11.5%, 3.7% and 3.5%, respectively). In contrast, RRs were lower in the SRC than in the CA for anti-infective agents (22.9%) due to the poor redemption of medicines prescribed for children or young adults. Despite the overall modest differences in redemption ratios, some ATC groups showed remarkable differences. Those include cardiovascular, alimentary and musculoskeletal drugs. Conclusion: Redemption of prescriptions was significantly higher among Roma people living in SRC than among those living in CA. The better redemption of cardiovascular and alimentary tract drugs was mainly responsible for this effect. These findings contradict the stereotype that the Roma do not use health services properly and that prescription nonredemption is responsible for their poor health.